Micro-catchment water harvesting and moisture conservation techniques for apple (Malus domestica) production under rainfed condition - KUMAR, DINESH; AHMED, N; SRIVASTAVA, K K; SINGH, S R; HASSAN, AAMIR (The Indian Journal of Agricultural Sciences, 2026)
A field experiment was conducted during 2009-10 and 2010-11 on influence of micro-catchment rain water harvesting and moisture conservation techniques for apple production under rainfed condition. Result indicated maximum plant height (2.94 m), TCSA (87.07 cm2), canopy volume (3.73 m3), annual shoot growth (69.96 cm), fruit yield (23.44 kg/tree and 14.65 tonnes/ha) were recorded in full moon water harvesting system and minimum in control. Among mulches, plastic mulch performed better in respect to TCSA (84.26 cm2), canopy volume (2.71 m3), annual shoot growth (63.34 cm), fruit yield (19.36 kg/tree and 12.10 tonnes/ha) respectively. Maximum soil moisture content was estimated in full moon water harvesting system followed by half moon. Among mulches, plastic mulch conserved more moisture than organic mulch and no mulch during fruit growth and maturation stage. Interaction effect of full moon water harvesting system + plastic mulching showed significantly maximum vegetative growth, fruit yield and soil moisture content in apple.